THE IMPLEMENTATION OF ICT INTEGRATION IN TEACHING ENGLISH BY HIGH SCHOOLS TEACHERS IN RELATION TO THEIR STUDENTS’ ENGLISH ACHIEVEMENT IN KOTA BENGKULU - Nila Kencana (English Education Study Program Faculty of Teacher Training and Education, 2017)
ABSTRACT The main purposes of study were to know the teachers’ understanding about ICT and its implementation in their instructional practice and the possible problems faced. Then, was there any correlation between teachers’ understanding about ICT and its implementation to the students’ achievement. The other purpose was to see whether the use of ICT influenced students’ achievement in Bengkulu. The sample consisted of 172 senior high schools English teachers and 438 tenth grade students. The data of this study were gained through the instruments: questionnaire, observation, test and interview. Data analysis was done in two stages. The result of this study showed that the implementation of ICT integration in teaching English by senior high school teachers in Kota Bengkulu had been started but it was still in the level of less favorable in all phases of instructional practice (planning, implementing, evaluating and reflecting). There were many problems faced by the teachers in integrating ICT in their teaching practice in terms of internal problems and the school policy.